The Vigilance Screening Tool in The Workplace: Scoping Review - Sugiarta, Iwan; Fitriani, Dewi Yunia; Mansyur, Muchtaruddin (Occupational and Environmental Medicine Journal of Indonesia, 2023)
VIGILANCE SCREENING TOOLS IN THE WORKPLACE: SCOPING REVIEW ABSTRACT Background: Vigilance performance examination is currently used widely in many disciplines, neurophysiology, sleep medicine, psychology to its application to workers whose daily activities require prime vigilance. A more objective inspection of vigilance has not yet become a routine screening examination for workers to detect decreased vigilance as part of a fit-to-work assessment, but only in the form of research / study using a partial sampling technique. The aim is to provide an overview of vigilance screening tools in the workplace, its terminologies and how the process of maintaining quality such as calibration and validation. Methods: A literature search was independently conducted from the Pubmed database. We are looking for only articles that meet the following criteria: discussions on the terminology of vigilance, or research on workers that use vigilance examination tools, or research that develops its examination tools. Results: Three articles were found that specifically discussed the term vigilance, 30 studies on workers that used vigilance performance examination tools, and 15 studies discussing the development of these tools. The definition of vigilance is still not firmly established and has been used interchangeably and leading to confusion. Workplace research has used product-based smart devices rather than dedicated hardware, as well as a number of studies that have focused on tools development. Conclusion: Vigilance is the capability to be aware of potentially relevant or capability to be sensitive to unpredictable changes in one's environment including a quantitative and a temporal dimension. Although vigilance testing may not pinpoint the exact cause of vigilance decrement, using it as a screening tool in workplace holds great potential. Smart-device-based tools are relatively easy to obtain and inexpensive, but face enormous challenges related to calibration issues, validation issues, manufacturer's service of life, and firmware updates. It's important to consider vigilance screening tools with low-cost, portable, robust, future-proof, and easily validated with clear calibration or validation methods. Keywords: alertness, neuropsychological tests, psychomotor performance, reaction time, vigilance